Arguments for equipping ДТ-75М tractor carriage with recuperative elements by means of mathematical simulation - Posmetiev V. I.; Tarasov E. А.; Snyatkov Е. V.; Latysheva М. А. (Mathematics and mechanics. Physics, 2007)
Заглавие с титульного листа